Developing of the electronic educational and methodological complex “Automotive design” for the professional training of future teachers of vocational training in the field of transport (Educational Dimension, 2020)
The article analyzes the essence of the concept of “electronic educational and methodological complex” and defines its structure, which consists of interconnected components that ensure the process of assimilation and consolidation of educational information and the implementation of automated pedagogical monitoring. The main didactic principles of designing electronic educational and methodological complexes are determined, in particular: science, clarity, accessibility and feasibility, systematicity and consistency, strength of acquired knowledge, problems, independence and activity of learning. The main requirements for electronic educational software, which have been also taken into account when creating the EEMC “Automotive Design”, are outlined: scientific content, purposefulness, openness, motivation, individualization of learning, creativity and more. Four stages of designing EEMC of the discipline “Automotive Design” are described, which consists of educational and methodological, control and diagnostic, and information and searching modules, has a relatively stable means of communication between them and provides a systematic learning process of students through additional independent or distance mastering of educational material with the help of a computer. It is noted that the implementation in the software of educational purposes of modern computer graphics, a variety of visual aids forms and develops visual thinking of the future teachers of vocational training. The use of EEMC contributes to the formation of information culture of the students, readiness for the widespread use of ICT tools in future professional activities.